Dynamics of morphological, immunological and histological changes in microsporіа in guinea pigs - Y. V. Kisera; Y. V. Martyniv; B. V. Gutyj (Regulatory Mechanisms in Biosystems, 2021)
Microsporіа affect different species of animals and humans. The high contagiousness of the pathogen determines the relevance of research into this disease. Microsporum canis is the pathogen that most often causes microsporia. Weakened functions of the immune system and violation of the epithelial barrier of the skin are a favourable factor that causes microspores. The main source of infection is cats, which are involved in the storage and transmission of the pathogen. To clarify the dynamics of morphological, immunological and histological changes in microsporia, blood and skin studies of guinea pigs infected with M. canis were carried out. The animals were divided into two groups of 6 guinea pigs (healthy and sick). Test material (blood and skin) was taken from clinically healthy and sick animals 21 and 42 days after infection. The number of erythrocytes and leukocytes was determined by counting them in the Goryaev chamber, the hemoglobin content – by the method of cyanide hemoglobin. The leukogram was derived based on the counting and differentiation of 200 leukocyte cells in blood smears. Material for histological examination (pieces of skin) was fixed in 10–12% cooled solution of neutral formalin, followed by pouring in paraffin according to the scheme proposed by G. A. Merkulov. The obtained results demonstrated that leukocytosis developed in guinea pigs with microsporia on the 21st and 42nd days; the number of rod-shaped neutrophils increased, that of segmental neutrophils decreased, and that of ESR increased. The immune response to the course of microsporia was manifested in an increase in the percentage of T-lymphocytes, T-suppressors and a decrease in T-helper cells and an increase in T-killers compared with healthy animals. Histological examination showed that on the 21st day after infection, hyphae and spores of the fungus M. canis were localized in the skin. There is swelling of the dermis, stratification of collagen fibers and the accumulation of inflammatory infiltrates around the hair follicles. On the 42nd day, the infiltration spread and dystrophic changes in the skin occurred in the form of desquamation of the epidermis and the formation of acanthosis and hyperkeratosis on the surface of the dermis. The conducted research will allow further assessment of the course of microsporia under the action of various drugs and help establish the most effective method of treatment.